WOMEN’S PARTICIPATION IN DECISION-MAKING AMONG FISHMONGERS IN THE EFFUTU MUNICIPALITY OF GHANA - Adiikanbasi, P. (UDS International Journal of Development, 2018)
Both qualitative and quantitative data collection techniques were used to obtain data from fishmongers and non-fishmongers in the Effutu Municipality of Ghana, the study indicates that change in women’s socio-economic status can ameliorate women’s hardship and that women’s access to income alone cannot increase their participation in decision-making both at the household and community levels. The study also reveals that at the household level, both fishmongers and non-fishmongers in the Effutu Municipality do not participate in reproductive decisions. The study recommends that development agents should design policy interventions on livelihood empowerment intervention. Key words: Women empowerment, Poverty reduction, Fishmongers, Decision – making